Federal Tax Handbook/Studies in Federal Taxation/Federal Income Tax Accounting (Book). - Smith, Dan Throop (The Accounting Review, 1941)
Abstract Reviews several books. "Federal Tax Handbook," by Robert H. Montgomery; "Studies in Federal Taxation," by Randolph E. Paul; "Federal Income Tax Accounting," 2nd ed., by Stewart Y. McMullen.